Monitoring Kinerja Jaringan Kampus 2 Politeknik Negeri Ujung Pandang Menggunakan Aplikasi Solarwinds - Litha, Arni; Marampa, Gresia Eunike; Duyo, Rizal A; Yuniarti, Yuniarti; Sakir, Riesa Krisna Astuti (Jurnal Teknologi Elekterika, 2023)
The internet network on campus 2 of the Ujung Pandang State Polytechnic (PNUP) often experiences interference with the internet network so that it becomes a complaint from students, lecturers and staff on campus. the network on campus is often down and it is difficult to access internet services to access the internet. So this study aims to measure the parameters of the internet network on campus using the solarwinds application. to analyze the results of monitoring network performance based on the parameters measured. To be able to determine the performance of the campus network 2 PNUP, it is necessary to analyze it by measuring the parameters of network latency, packet loss, throughput and bandwidth usage. Based on the measurement results on holidays in all buildings, the network latency and packet loss results were in very good condition, as well as the throughput and bandwidth were in good condition. By obtaining the overall condition is good. Whereas on the active day of lectures in all buildings, the results showed that network latency was not good and packet loss was in good condition, although there was often an increase in packet loss at certain hours of 100% but it returned to stability, and throughput and bandwidth were in poor condition. By obtaining the overall condition that is not good.